Pengaruh Pemberian Soal Open-Ended Terhadap Kemampuan Penalaran Matematis Siswa (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2013)
AbstrakPenelitian eksperimen ini bertujuan untuk mengetahui perbedaan peningkatan kemampuan penalaran matematis antara siswa yang diberi soal open-ended dengan siswa yang diberi soal rutin, perbedaan peningkatan kemampuan penalaran matematis ditinjau dari level siswa, serta interaksi antara pemberian soal dan level pengetahuan awal matematika (PAM) siswa dalam peningkatan kemampuan penalaran matematis siswa. Pengumpulan data dilakukan melalui tes. Nilai gain diperoleh dari rumus Meltzer dengan hasil: untuk kelas eksperimen nilai gain minimum = -0,07 dan maksimum 0,86, sedangkan untuk kelas kontrol nilai gain minimum = -0,63 dan maksimum 0,55. Dari hasil penelitian disimpulkan bahwa (1) terdapat perbedaan signifikan dalam peningkatan kemampuan penalaran matematis siswa antara siswa yang diberi soal open-ended dan siswa yang diberi soal rutin, (2) terdapat perbedaan signifikan dalam peningkatan kemampuan penalaran matematis antara siswa pada level pengetahuan awal matematika tinggi, sedang, dan rendah. Kata kunci : penelitian eksperimen, penalaran matematis, soal open-ended AbstractThe aim of this experimental study was to determine differences in mathematical reasoning skills improvement among students who were given open-ended questions with the students who were given a routine matter, differences in mathematical reasoning ability improvement in terms of the level of students , as well as the interaction between the administration and the level of prior knowledge about mathematics ( PAM ) students in improving students' mathematical reasoning abilities . Data collected through the test . Gain value obtained from the formula Meltzer with the results : for the experimental class minimum gain value = -0.07 and maximum 0.86 , while the value of the gain control for a class of minimum and maximum = -0.63 From the results of the study concluded that (1) there is a significant difference in the improvement of students' mathematical reasoning ability between students who were given open-ended questions and students are given a routine matter , (2) there is a significant difference in the improvement of mathematical reasoning ability among the students at the level of initial knowledge of mathematics high , medium , and low. Keywords : experimental studies , mathematical reasoning , open-ended questions